Accuracy of Capillary and Arterial Whole Blood Glucose Measurements Using a Glucose Meter in Patients under General Anesthesia in the Operating Room. (September 2017) - Karon, Brad S.; Donato, Leslie J.; Larsen, Chelsie M.; Siebenaler, Lindsay K.; Wells, Amy E.; Wood-Wentz, Christina M.; Shirk-Marienau, Mary E.; Curry, Timothy B.
Abstract : Background: The aim of this study was to evaluate the use of a glucose meter with surgical patients under general anesthesia in the operating room. Methods: Glucose measurements were performed intraoperatively on 368 paired capillary and arterial whole blood samples using a Nova StatStrip (Nova Biomedical, USA) glucose meter and compared with 368 reference arterial whole blood glucose measurements by blood gas analyzer in 196 patients. Primary outcomes were median bias (meter minus reference), percentage of glucose meter samples meeting accuracy criteria for subcutaneous insulin dosing as defined by Parkes error grid analysis for type 1 diabetes mellitus, and accuracy criteria for intravenous insulin infusion as defined by Clinical and Laboratory Standards Institute guidelines. Time under anesthesia, patient position, diabetes status, and other variables were studied to determine whether any affected glucose meter bias. Results: Median bias (interquartile range) was −4 mg/dl (−9 to 0 mg/dl), which did not differ from median arterial meter bias of −5 mg/dl (−9 to −1 mg/dl; P = 0.32). All of the capillary and arterial glucose meter values met acceptability criteria for subcutaneous insulin dosing, whereas only 89% (327 of 368) of capillary and 93% (344 of 368) arterial glucose meter values met accuracy criteria for intravenous insulin infusion. Time, patient position, and diabetes status were not associated with meter bias. Conclusions: Capillary and arterial blood glucose measured using the glucose meter are acceptable for intraoperative subcutaneous insulin dosing. Whole blood glucose on the meter did not meet accuracy guidelines established specifically for more intensive ( e.g., intravenous insulin) glycemic control in the acute care environment. Abstract : The authors have performed a study in the operating room of new glucose meter technology with hematocrit and interference correction on capillary and arterial blood samples in comparison with reference arterial whole blood glucose measurements by a blood gas analyzer. The authors found that arterial and capillary blood glucose measurements with the glucose meter did not meet established guidelines for intensive blood glucose control, suggesting caution be exercised when using glucose meters for intravenous glycemic control protocols.